2015
DOI: 10.1089/cyber.2015.0110
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Parental and Adolescent eHealth Literacy and Online Health Information Seeking in Taiwan

Abstract: This study examined the relationship between parental and adolescent eHealth literacy and its impact on online health information seeking. Data were obtained from 1,869 junior high school students and 1,365 parents in Taiwan in 2013. Multivariate analysis results showed that higher levels of parental Internet skill and eHealth literacy were associated with an increase in parental online health information seeking. Parental eHealth literacy, parental active use Internet mediation, adolescent Internet literacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 29 publications
8
84
2
Order By: Relevance
“…However, Barnes and Davies (34) reported a mean reading grade level of 13 for 63 online and paper materials on thyroid nodule evaluation and management. Most of these materials had ‘extensive or serious shortcomings’, which lead to uncalled anxiety and misconceptions (35,36). With limited patient encounter time, there is not enough opportunity for all questions to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, Barnes and Davies (34) reported a mean reading grade level of 13 for 63 online and paper materials on thyroid nodule evaluation and management. Most of these materials had ‘extensive or serious shortcomings’, which lead to uncalled anxiety and misconceptions (35,36). With limited patient encounter time, there is not enough opportunity for all questions to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be shown that eHealth Literacy scores are higher for students who had been actively involved in searching for health information online than for non-experienced peers [25]. Similarly, data suggest that parental online health information seeking is positively associated with adolescents’ eHealth Literacy and engagement in online searches for health information [26]. These findings support the conclusion that eHealth Literacy skills are strongly shaped by exposure to technology, the Internet, and online health information sources in particular.…”
Section: Media Health Literacy and Ehealth Literacy In Contextmentioning
confidence: 99%
“…Several findings suggest that eHealth Literacy levels are shaped and can possibly be improved through guidance in online health information seeking activities by more experienced users as well as in structured learning environments. For example, Chang and colleagues [26] showed that active parental mediation of their adolescent children’s Internet use predicted adolescents’ eHealth Literacy. Participants in focus groups conducted among Spanish primary school students reported use of the Internet as a tool for learning about health topics and habits, but preferred their searches to be guided and supervised by their parents to promote their efficacy and confidence in dealing with online (health) content [43].…”
Section: Media Health Literacy and Ehealth Literacy In Contextmentioning
confidence: 99%
“…It has been shown that eHealth Literacy scores are higher for students who had been actively involved in searching for health information online than for nonexperienced peers [38]. Similarly, data suggest that parental online health information seeking is positively associated with adolescents' eHealth Literacy and engagement in online searches for health information [39]. These findings support the conclusion that eHealth Literacy skills are strongly shaped by exposure to technology, the Internet, and online health information sources in particular.…”
Section: Complexity Of Systems and Environmentsmentioning
confidence: 51%
“…Several findings suggest that eHealth Literacy levels are shaped and can possibly be improved through guidance in online health information seeking activities by more experienced users, as well as in structured learning environments. For example, Chang and colleagues [39] showed that active parental mediation of their adolescent children's Internet use predicted adolescents' eHealth Literacy. Participants in focus groups conducted among Spanish primary school students reported use of the Internet as a tool for learning about health topics and habits, but preferred their searches to be guided and supervised by their parents to promote their efficacy and confidence in dealing with online (health) content [41].…”
Section: Social Networkmentioning
confidence: 99%